Turkish Ro-Ro Traffic in the Port of Trieste - Torbianelli, Vittorio A. (Promet - Traffic&Transportation, 2012)
This article gives an economic and organisational analysis of the intermodal transport se1vice by means of Ro-Ro vessels between Turkey and central Europe through the port of Trieste.Many traits of this service are innovative, at least in the Mediterranean.To mention but a few: the geographical area it connects,the rapid geo-political evolution, the independent managingof the maritime route by a cons01tium of road transport companies, the use of combined road/ rail transport to reachthe European market, the air transfer of drivers, the transformationto the structure of the companies, etc. This service offersindeed a valuable example- not only because of its supeliorlogisticalefficiency compared to the road or container ship options-for the future of transport between Europe (in particularcentral- eastern European count1ies) and the new markets inthe Levant, located behind the Eastern Mediterranean shores.